Generation of eGFP and Cre knockin rats by CRISPR/Cas9. (13th August 2014) - Ma, Yuanwu; Ma, Jing; Zhang, Xu; Chen, Wei; Yu, Lei; Lu, Yingdong; Bai, Lin; Shen, Bin; Huang, Xingxu; Zhang, Lianfeng
<x xml:space="preserve">Abstract</x> The type II bacterial CRISPR/Cas [clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated (Cas)] system is a very valuable genome engineering tool, which has been widely used in genome editing of a variety of organisms. Previously, we generated floxed alleles in rats by CRISPR/Cas9. Here, we successfully use a two‐cut strategy with one circular vector, which contains the exogenous cDNAs with homology arm regions, in generating knockin rats at the Trdmt1, Nestin and Cck loci. The efficiency of CRISPR/Cas9‐mediated knockin was up to 54%. Furthermore, by crossing the Nestin‐Cre rat with the Dnmt3b floxed rat and Cck‐Cre with the Dnmt1 floxed rat, we detected Cre/loxP‐mediated recombination in the F1 generation of rats. We also show that the knockin alleles were germline transmitted. These results provided a simple and flexible engineering strategy for the establishment of knockin rats.